`Dukungan Kualitas Power Endurance Dan Fleksibilitas Panggul Terhadap Kecepatan Renang 50m Gaya Kupu Kupu - Ishlah, Rifandi Hanif; Imanudin, Iman; Zaky, Mohammad (Dharmas Journal of Sport, 2025)
This study aims to examine the relationship between Power Endurance Quality Support and Hip Flexibility to 50m Butterfly Swimming Speed. This research method uses a quantitative method with a correlational research type, the sample used was 10 athletes from the Bandung Swimmingstar swimming club aged 12-14 years. The results showed that power endurance quality support and hip flexibility had a significant relationship to 50m butterfly swimming speed. The Pearson correlation coefficient showed that power endurance quality had a significant relationship to swimming speed with a value of 0.00 <0.05 (r = -918), hip flexibility also had a significant relationship to 50m butterfly swimming speed with a value of 0.00 <0.05 (r = -905). With these results, it can be concluded that power endurance and hip flexibility are important factors in increasing 50m butterfly swimming speed. Therefore, it is recommended for coaches and swimmers to pay attention to the quality of power endurance and hip flexibility in swimming training programs.